Challenging Stereotypes with Media and Information Literacy in Mexico - Flores Michel, Julieta; Gonzalez Treviño, Margarita Emilia; Gutiérrez Leyton, Alma Elena (2019)
Information overload that affects digital natives and other generations in the 21st century makes it difficult for recipients to analyze the information’s truthfulness and quality. In this context, items of fake news pass as facts that could be interpreted as true, which may result in serious issues for the social fabric, especially if immersed in unstable or troublesome political and economic contexts. Still, the problem with disinformation is not limited to fake news because, even when content comes from trustworthy sources and verifiable facts, there are filters that present a subjective, biased and deformed reality. Within this context, we are submitting an example of a positive practice in media literacy targeting Research Methodology students at the Faculty of Communication. During this project, students analyzed the way women and men are shown on the cover of a local printed newspaper El Porvenir in the city of Monterrey, Mexico. In broad strokes, the results found a preferen...